Health Impacts and Research Ethics in Female Trafficking - Dhital, S R; Aro, R A (Journal of Nepal Health Research Council, 2011)
Female trafficking is a social and public health problem, associated with physical and sexual abuse, psychological trauma, injuries from violence, sexually transmitted infections, adverse reproductive outcomes and substance misuse. It faces several challenges ranging from the hidden nature of the problem to ethical and human rights issues. The objectives of this paper are to analyze health impact of trafficking; ethical and research issues and anti-trafficking strategies in the Nepalese context. We collected published and unpublished data assessing the public health, ethical burden and research needs from different sources. Trafficked female involved in sex-industry that face grave situationas depicted and it might a reservoir of sexually transmitted diseases. Ethical issues related to survey of assessing the burden are difficult to carry out. The best ways to prevent and control these problems are to enhance anti- trafficking laws and raise awareness, empower and mobilize females and establish organizational capacity. Keywords: empowerment, female trafficking, health issues, Nepal